(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
In the process of storing vegetables, it is important to know their physical properties and to use these properties on a scientific basis. The physical properties of vegetables are of great importance in their harvesting, transportation and storage. The physical properties of vegetables are their evaporation and sweating. thermal properties, mechanical hardness, flowability. varieties by themselves include separation, porosity, etc. In the process of storage, products evaporate a lot of water, sweat, and as a result, wither.